Ex vivo stimulace buněčné imunity pomocí mRNA u pacientů s vysokým rizikem onemocnění, způsobeného lidským cytomegalovirem (HCMV) po transplantaci hematopoetických kmenových buněk - Němečková, Šárka; Vítek, Antonín; Žůrková, Kamila; Dušková, Martina; Babiarová, Katarína; Kryštofová, Jitka; Hainz, Petr; Marková, Markéta; Marinov, Iuri; Macková, Jana (2016)
Here, we propose to prepare mRNA vaccine against a number of candidate immunogenic CMV proteins. The vaccine will include antigen presenting cells electroporated mRNA coding for viral protective antigens and immunostimulatory molecules known to enhance activation of T-cells directed to Th1. To evaluate the protective potential of each CMV vaccine component the magnitude of CMV T-cell response of seropositive donors or patients after HSCT to each individual protein will be monitored and analyzed in the context of CMV DNA levels of HSCT patient. Tcell response will be characterized phenotypicaly and functionally by multiparametric flow cytometry. The result of the study will enable to elaborate immunotherapy protocol under good manufacturing practise conditions. mRNA vaccine will be also used for monitoring in CMV-specific T cell response of patients after HSCT.
Závěrečná zpráva o řešení grantu Interní grantové agentury MZ ČR
Keywords: Hematopoietic Stem Cell Transplantation; T-lymfocyty; transplantace hematopoetických kmenových buněk; RNA, Messenger; Immunosuppression Therapy; imunosupresivní léčba; antigeny CD8; CD4 Antigens; Immunotherapy, Adoptive; T-Lymphocytes; imunoterapie adoptivní; antigen prezentující buňky; Immunity, Cellular; messenger RNA; molekulární biologie, molekulární medicína; Antigen-Presenting Cells; hematologie a transfuzní lékařství; cytomegalovirové infekce; buněčná imunita; Cytomegalovirus Infections; alergologie a imunologie; CD8 Antigens; antigeny CD4